Pengaruh Pembelajaran Metode al Birru terhadap Kemampuan Menghafal Juz ‘Amma Siswa Kelas VII SMPIT al Huda Wonogiri - Rizkiana Hudzaifah; M. Ja’far Nashir; Muin Abdullah (MODELING: Jurnal Program Studi PGMI, 2023)
This study examines the Effect of Learning the Al Birru Method on the Ability to Memorize Juz 'Amma at SMPIT Al Huda Wonogiri. The purpose of this study was to find out how the learning of the Al Birru method and the students' ability to memorize Juz 'Amma was, and how strong the influence of learning the Al Birru method was on the students' ability to memorize Juz 'Amma. The number of samples selected was 92 grade VII students of SMPIT Al Huda Wonogiri. The analytical technique used is a descriptive technique to describe the results of the research conducted. To test the validity of the data used validity and reliability tests. The type of approach used in this research is quantitative. As for data collection with documentation and questionnaires.